Exact Combined Solutions for the (2+1)-Dimensional Dispersive Long Water-Wave Equations. (4th May 2020) - Wei, Yi; Zhang, Xing-Qiu; Shao, Zhu-Yan; Gu, Lu-Feng; Yang, Xiao-Feng
Abstract : The homogeneous balance of undetermined coefficient (HBUC) method is presented to obtain not only the linear, bilinear, or homogeneous forms but also the exact traveling wave solutions of nonlinear partial differential equations. Linear equation is obtained by applying the proposed method to the (2 + 1 )-dimensional dispersive long water-wave equations. Accordingly, the multiple soliton solutions, periodic solutions, singular solutions, rational solutions, and combined solutions of the (2 + 1 )-dimensional dispersive long water-wave equations are obtained directly. The HBUC method, which can be used to handle some nonlinear partial differential equations, is a standard, computable, and powerful method.